Model for Surveillance and Promotion of Nutrition among Preschool Children at Child Development Center, Muang District, Songkhla Province: Chanyanuch Klerlhee - Klerlhee, Chanyanuch; prommul, jirarat; Perngyai, Chutima; Intaranarong, Kritika; Namjaroen, Terdsak (Princess of Naradhiwas University Journal, 2024)
The purposes of this research and development were to examine the state of nutrition among preschool children and develop a model for surveillance and promotion of nutrition among them through the processing of two phases: the first phase and the second phase. The first phase was analyzing preschool children’s nutritional status. Samples for the quantitative study were 166 preschool children and their parents at the child development center in Muang District, Songkhla Province using a sampling without replacement method. The research instruments were: 1) Personal data; 2) growth development record form; 3) nutrition record form; and 4) family supplying food assessment and children eating behavior assessment. Experts validated each instrument by determining that the content validity index (IOC) equaled 1. Alpha's Cronbach coefficient 's reliability index was equal to.84. Frequency, percentage, mean, and standard deviation were all used in data analysis. Samples for the qualitative study were six delegates from each child development center, for a total of 36 people. Participation in in-depth interviews and participation observation of individuals who were responsible for nutrition care were used. The second phase was four-step approach of development model of surveillance and promotion of nutrition among preschool children included: 1) instruction regarding ' preschool children growth development, and nutrition to teachers, babysitters, and parents; 2) the researcher presented the situation analysis data. The samples consisted of 166 preschool children and their parents from the child development center, Muang District, Songkhla Province; 3) the samples were assigned to a small group for brainstorming regarding a model of surveillance and promotion of nutrition among preschool children; and 4) the researcher used the small group brainstorming information to develop a model of surveillance and promotion of nutrition among preschool children at child development center. The results demonstrated that almost all preschool children experienced problems with vegetable consumption, malnutrition (fat, thin, or petite), and a predilection for crunchy snacks. A developed model of surveillance and promotion of nutrition had involved the child development center and parents for participation in the process to provide caring recommendations for meeting nutrition status criteria and enhancing the effectiveness of malnutrition surveillance.